Priority Queuing on the Docket: Universality of Judicial Dispute Resolution Timing - Mukherjee, Satyam; Whalen, Ryan (Frontiers in Physics, 2018)
This paper analyzes court priority queuing behavior by examining the time lapse between when a case enters a court's docket and when it is ultimately disposed of. Using data from the Supreme courts of the United States, Massachusetts, and Canada we show that each court's docket features a slow decay with a decreasing tail. This demonstrates that, in each of the courts examined, the vast majority of cases are resolved relatively quickly, while there remains a small number of outlier cases that take an extremely long time to resolve. We discuss the implications for this on legal systems, the study of the law, and future research.